Formation of metre-scale bladed roughness on Europa's surface by ablation of ice. Issue 12 (December 2018) - Hobley, Daniel; Moore, Jeffrey; Howard, Alan; Umurhan, Orkan
Abstract On Earth, the sublimation of massive ice deposits at equatorial latitudes under cold and dry conditions in the absence of any liquid melt leads to the formation of spiked and bladed textures eroded into the surface of the ice. These sublimation-sculpted blades are known as penitentes. For this process to take place on another planet, the ice must be sufficiently volatile to sublimate under surface conditions and diffusive processes that act to smooth the topography must operate more slowly. Here we calculate sublimation rates of water ice across the surface of Jupiter's moon Europa. We find that surface sublimation rates exceed those of erosion by space weathering processes in Europa's equatorial belt (latitudes below 23°), and that conditions would favour penitente growth. We estimate that penitentes on Europa could reach 15 m in depth with a spacing of 7.5 m near the equator, on average, if they were to have developed across the interval permitted by Europa's mean surface age. Although available images of Europa have insufficient resolution to detect surface roughness at the multi-metre scale, radar and thermal data are consistent with our interpretation. We suggest that penitentes could pose a hazard to a future lander on Europa. Sublimation rates of water ice in equatorial regions of Jupiter's moon Europa are sufficient to sculpt bladed terrain that would pose a hazard to a potential lander mission.